Some measures to optimize and make efficient the international maritime transport - Oprescu Georgiana (Technium Social Sciences Journal, 2020)
Through this study I aimed to address the different concepts of international maritime transport in terms of its legal, economic, administrative and organizational evolution over time, globally. International maritime transport is of extraordinary importance due to the fact that through it the states have the possibility to develop due to the different situations encountered in the civil circuit, and implicitly the commercial one is constantly enriched with new elements. Despite the fact that there are many countries that are not riparian, it is absolutely necessary to have regulations in the maritime field, given the importance of the safety of the trade in goods. Even if, initially, in Romania there was no code of maritime law, there was no autonomous legislation of maritime law, there is, however, a tradition in this field based on commercial law whose content, over time, maritime law has become autonomous as a science and field of application. The history of trade is, to a large extent, the very history of civilization. In the beginning, human needs were few and very simple, limited to obtaining food and clothing. But as he progressed on the evolutionary scale of intelligence, humans demands grew, wanting more than minimal comfort. Trade is one of the methods that producers, sellers and consumers adopt at different times in order to meet their various needs. Due to the fact that no civilized society will be able to actually produce all the goods it consumes based on material difficulties, lack of natural resources, coal, wood, oil, lack of climate specific to the cultivation of a certain variety of vegetables and fruits, etc., maritime transport offers the chance and the connection between civilizations, cultures, continents, thus succeeding in the transport of goods and products to other nations. World trade has always been a solution to the problems and strategies regarding the transport of raw materials urgently needed for the evolution of society and implicitly of industry. Precisely for this reason and to encourage world trade, over the centuries, a number of measures have been taken to make it more efficient, such as measures planned over time, which have proven to be beneficial strategies for the evolution of the economy. and world industry. One of the measures that has had a positive impact on maritime trade and that I will develop in my study, in comparison, is the enlargement of the Suez Canal and the Panama Canal.